ANALYZING THE USE OF HYPERLOCAL MARKETING OF STREET FOOD STARTUP BUSINESS IN MANADO - Aruan, Carina; Worang, Frederik G.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Nowadays, everything is practically inseparable from technology, and also includes the marketing process now became digital. There are several digital marketing strategies, and one of them is hyperlocal marketing strategy. Hyperlocal marketing can help the startup business to get an advantage by using the area they know best to bring in more customers. Hyperlocal marketing can reach customers digitally. This study aims to analyze whether the use of hyperlocal marketing of street food startup business in Manado is effective or not. This research takes a qualitative approach by conducting interviews with 10 street food startup business owners in Manado as the respondents, which were chosen through purposive sampling. Findings of this research to know more about the use of hyperlocal marketing of street food startup business from business owners experienced. The results of this research are the use of hyperlocal marketing can affect the business sales, also effective to all street food startup businesses who become a respondent in this research. Street food startup businesses in Manado should improve their knowledge about the use of hyperlocal marketing, so that the use of hyperlocal marketing can work even better to get more customers and can increase the sales.Â Keywords: hyperlocal marketing, digital marketing, street food, startup business